Strategy of Integrating Buildings with Smart Systems - Dr. Shagin Musa Saleh Mahmoud, Dr. Eleyan Issa Jamal Issa (International Journal of Advanced Science and Technology, 2020)
Magical brilliance between information capabilities and environmental control capabilities and energy consumed, which defines intelligent buildings. It becomes inevitable and things common in various areas of architecture such as government, public service and productivity. Even at the city and urban planning level. This can be attributed primarily to the vital role of computers in all aspects of life so that air-conditioned buildings are able to meet the needs of the consumer. It is also necessary to provide the conditions of comfort, leisure and entertainment, with respect to smart buildings depends primarily on the design and work of internal structure and utility and service systems. These are technologically advanced technologies that rely on high-level development to cope with the changes and developments in the information revolution in order to give the fruits of ideal and interactive buildings that provide the resident comfort environment for the ability to perform their tasks very well.